2010
DOI: 10.4149/gpb_2010_04_402
|View full text |Cite
|
Sign up to set email alerts
|

The hypothesis of the main role of H2S in coupled sulphide-nitroso signalling pathway

Abstract: Abstract. As a part of the nitroso signalling pathway, nitroso-compounds serve as stores and carriers of NO; as part of the sulphide signalling pathway, bound sulfane-sulphur compounds serve as stores and carriers of H 2 S. Here we hypothesise a coupled sulphide-nitroso signalling pathway, in which H 2 S plays a main role. H 2 S releases NO from the endogenous S-nitroso-compounds nitrosocysteine, nitroso-acetylcysteine and nitroso-albumin. Relaxation of noradrenaline-precontracted aortic rings by H 2 S is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
(70 reference statements)
2
22
0
Order By: Relevance
“…We can assume that a similar mechanism is also valid for the inhibitory effects of CYS and GSH. This assumption is supported by our reported results that pre-treatment of serum albumin, Cys, NAC and lipids with H 2 S results in sulfur binding to these molecules, and these modified sulfur compounds release • NO from nitroso-compounds directly and/or through reliberated H 2 S (Bertova et al 2010). Our observation that 400 µmol/l Cys was not more efficient in decreasing GSNO decomposition than 200 µmol/l Cys (Fig.…”
Section: Effect Of Cys Nac Gsh Gssh and Met On H 2 S-induced Gsno supporting
confidence: 80%
See 1 more Smart Citation
“…We can assume that a similar mechanism is also valid for the inhibitory effects of CYS and GSH. This assumption is supported by our reported results that pre-treatment of serum albumin, Cys, NAC and lipids with H 2 S results in sulfur binding to these molecules, and these modified sulfur compounds release • NO from nitroso-compounds directly and/or through reliberated H 2 S (Bertova et al 2010). Our observation that 400 µmol/l Cys was not more efficient in decreasing GSNO decomposition than 200 µmol/l Cys (Fig.…”
Section: Effect Of Cys Nac Gsh Gssh and Met On H 2 S-induced Gsno supporting
confidence: 80%
“…These results support a hypothesis of a "coupled sulphidenitroso signalling pathway" (Bertova et al 2010). In spite of the fact that the steady-state free H 2 S concetrations in vivo are less than 20 nmol/l (Furne et al 2008), its storage forms, such as bound sulfane sulfur and acid-labile sulfide, may be critical in regulating H 2 S availability under different intracellular conditions (Ishigami et al 2009).…”
Section: Biological Significancesupporting
confidence: 70%
“…Experiments were carried out as previously described [8,9]. Briefly, preparations of thoracic aorta and arteria mesenterica superior (main branch) were prepared from male Wistar rats and mounted for recording of isometric tension changes in oxygenated (95% O2/5% CO2; 37°C) Krebsbicarbonate solution comprising (in mM) 118 NaCl, 5 KCl, 25 NaHCO3, 1.2 MgSO4, 1.2 KH2PO4, 2.5 CaCl2, 11 glucose, 0.032 CaNa2EDTA, pH 7.5.…”
Section: Measurement Of Rat Aorta Contractilitymentioning
confidence: 99%
“…Similarly, H2S can be stored in the form of sulfane sulfur and transported and released in response to a physiological stimulus [3]. A number of publications reported on the molecular interaction between H2S and NO or NO-donors [4][5][6][7][8][9][10][11][12][13][14], and H2S and NO were found to cooperatively regulate vascular tone by activating a neuroendocrine signaling pathway in which formation of nitroxyl (HNO) appears to play an important role [13]. Products of this H2S/NO interaction appear to have pronounced biological effects; however the nature of the reaction intermediates is currently unclear and many inconsistencies remain; for example, H2S donors were found to either potentiate or attenuate relaxation effect of NO donors in isolated aortic rings in vitro [15,16], or result in complete loss of vasodepressor activity in anesthetized rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no consensus regarding the anti-inflammatory ability or pro-inflammatory ability of H 2 S. In some researches, pretreatment of mice with H 2 S improved leukocyte rolling/ adhesion as well as neutrophil migration, which subsequently contributed to reduce bacteria levels and improve survival rate. 17 This suggested that endogenous H 2 S played a protective role in systemic inflammatory responses. The study by Li et al revealed that the damage of ALI/ARDS mouse was aggravated after NaHS was administered, which suggested the proinflammatory role of H 2 S. 4 In the current study, H 2 S is significantly lower in patients with ISS ≥ 25 compared with the patients with ISS ≤ 16.…”
Section: Groupmentioning
confidence: 99%